Cognitive Stylistic Analysis of Ariana Grande's Intro (End of the World) - Sianturi, Naomi Elisabeth; Tarigan, Abigail Chrissantha; Ariqah, Nabilah; Rangkuti, Rahmadsyah (Humanitatis : Journal of Language and Literature, 2024)
This study explores the application of cognitive stylistics in analyzing Ariana Grande’s song "Intro (End of theWorld)" through schema theory. Schema theory is employed to understand how listeners interpret the song’s lyrics by activating pre-existing mental frameworks. The background of this research includes examining rhetorical devices used by the artist, such as personification, similes, metaphors, and hyperbole, to convey complex emotions and ideas. The methodology consists of a detailed textual analysis of the lyrics, focusing on identifying and interpreting these devices concerning the song’s thematic elements. The findings indicate that the song addresses themes of relationship evaluation, self-discovery, and the intricacies of interpersonal connections. The metaphorical language, melodic and lyrical structure, and vocal delivery contribute to the song’s emotional depth and thematic complexity. The study concludes that the use of schema theory helps elucidate how these stylistic elements influence listeners’ understanding and emotional engagement with the song, enhancing their overall experience.